Olympic Athletes and Canadian Citizens to be Subjects of Physical Fitness Study - Rickard, Josephine M. (1976)
The press release announces physical education professor Claude Allard's "Study of Man in Motion," operating in conjunction with an anthropological study. A mobile van, including equipment supplied by Beckman Instruments, was to be dispatched to Montreal's Olympic Village to run various physiological tests on competing athletes, and later cross the country running similar tests in different regions.
Keywords: Analytical biochemistry; Glucose--Analysis; Université Laval; Olympic Games; Canadians; Metabolism; Athletes; Physiology; Beckman Instruments, Inc.; Université de Montréal